La financiación del deporte de alto rendimiento femenino en la CAPV (The financing of women’s high performance sports in the Basque Country) - Judit Martínez Abajo; Vizcarra Morales, María Teresa; María Gema Lasarte Leonet; Pilar Aristizabal Llorente (Retos (Madrid), 2021)
The financing of high-performance sports is a challenge today, especially for female athletes. They access scholarships and sponsorships, yet with more difficulties than their male peers. In institutions such as the Higher Sports Council, specific programs, such as that of women and sports, are developed. However, their effectiveness is not reviewed. Through 18 interviews and three discussion groups, the financing of the sports careers of several athletes from the Basque Country has been studied. Sportswomen have been given a voice to know their impressions of financial support or lack thereof throughout their sports careers. Some of the results from this study show that athletes claim to have little and late support, received through scholarships and sponsors, and highlight the need for greater financial support in their sports careers. They conclude that it is urgent to move towards professionalization in their sports careers to improve their effectiveness.